Optimalisasi Infrastruktur Cloud Networking melalui Integrasi SDN, NFV, dan Multi-Cloud - Fauzan Prasetyo Eka Putra; Noviyani Dwi Saputri; Fathur Rosi; Rohilia Loati (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
Cloud networking is a crucial element in the management of modern computer network infrastructure because it can increase service efficiency and flexibility. However, the successful implementation of cloud networking is highly dependent on the network architecture that supports optimal performance. This research conducted a literature study to review the development of computer network architectures that facilitate the implementation of cloud networking, by reviewing more than 50 recent publications related to software-defined networking (SDN), network function virtualization (NFV), and hybrid and multi-cloud models. The review shows that the integration of SDN and NFV is a major trend for designing adaptive and cost-effective network architectures, while the combination of hybrid and multi-cloud models improves scalability and redundancy. In conclusion, the adoption of SDN-NFV technology and mixed cloud deployment strategies have proven effective in optimizing the performance and management of cloud-based networks.